MENINGKATKAN HASIL BELAJAR SISWA MENERAPKAN MODEL MAKE A MACTH MATA PELAJARAN IPS POKOK BAHASAN MENCERITAKAN TOKOH TOKOH SEJARAH PADA MASA HINDUBUDHA DAN ISLAM DI INDONESIA DI KELAS VI SD NEGER0 040451 KABANJAHE TP 2018/2019 - Pelista Br Karo Sekali; Jainab Jainab (Universitas Quality, 2019)
This classroom action research was carried out to apply the Learning Model Make a Macth Social Studies Subject The Subject of Telling Historical Figures in the Hindu Hindu and Islamic Period in Indonesia in Class VI SD Negeri 040451 Kabanjahe Academic Year 2018/2019. The purpose of this study was to find out the Learning Implementation of students, knowing the mastery of student learning, knowing the improvement in student learning outcomes applying the Model Make a Match Social Studies Subjects Discussing Historical Figures in the Period of Hindu Buddhism and Islam in Indonesia in Class VI SD Negeri 040451 Kabanjahe Academic Year 2018/2019. The subject of this research is the keas VI totaling 30 people and the research object applies the Make a Macth Model. The instruments used are observation sheets and essay tests. Based on the results of the Cycle I study, the learning activities of the teacher obtained 60% sufficient criteria and the second cycle obtained 78% good criteria. , the activity of students in cycle I was obtained 68 values including sufficient criteria, and cycle II the activity value of students 84 criteria was good, completeness learning cycle I of 30 students 73% or 22 people completed, cycle II 27 people completed their study or 90% and increased learning outcomes 10% apply Learning Model Make a Macth Social Studies Subjects Discuss the Historical Figures in the Hindu Hindu and Islamic Period in Indonesia in Class VI SD Negeri 040451 Kabanjahe 2018/2019 Academic Year. Thus, this study can be concluded that, the implementation of good performance learning, student learning outcomes are completed thoroughly and increase applying Learning Model Make a Macth Social Sciences Subjects Discussing Historical Figures in the Period of Hindu Buddhism and Islam in Indonesia in Class VI Public Elementary School 040451 Kabanjahe Academic Year 2018/2019.